SOY PRODUCTIVITY DEPENDS ON GROWING TECHNOLOGY - Марініч, Любов; Бурлаєнко, Кирило (SWorldJournal, 2024)
Topicality. Ukraine is one of the leaders in the production of soybeans on the Eurasian continent and ranks first in Europe in terms of the number of bred and introduced varieties and constantly continues to increase the cultivated area occupied by the cu